The Implementation of Land Waqf Law in Indonesia and Malaysia as a Stage to Land Waqf Law Reform in Indonesia: A Comparative Study - Hakimah, Asma; Marom, Ruzian; Islamiyati, Islamiyati; Musyafah, Aisyah Ayu; Budiman, Achmad Arief (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2022)
Legal problems in the implementation of land waqf in the community are found in; wakif, status of waqf land, nadzir, wakif heirs, nadzir heirs, and land waqf institutions. Therefore, it is very important to conduct a research on A Comparative Study on the Implementation of Land Waqf Law in Indonesia and Malaysia as a Stage to Land Waqf Law Reform in Indonesia to analyze land waqf practices in Indonesia and Malaysia, then to compare and identify their similarities and differences. This research can provide ideas for the government in updating the land waqf law. This study used a comparative approach. The research data include primary and secondary data. The data were analyzed qualitatively. The results showed that there are some similarities of land waqf practices in Indonesia and Malaysia. These similarities are found in terms of ; its legal basis; forms of wakif and nadzir; as well as the position of the land waqf witness. Meanwhile, the difference lies in; land waqf management practices; government policy on waqf institutions; allotment, term, and settlement of land waqf disputes. By comparing Malaysian and Indonesia land waqf law practices, Indonesia can renew the land waqf law on the aspects of its legal rules and legal institutions.